Understanding the Financial Inclusion Moderating Effect on Negative Attitude of Muslim Population towards Banking Services in Tamil Nadu, India - F. , Abubecker; Khan, Mohsin; Waheed, Khalid (International Journal of Psychosocial Rehabilitation, 2020)
Financial inclusion, meanwhile, has turned into a progressively more important concern for a huge number of countries with wide-reaching effects. The Indian economy is growing, but ironically the rate of poor people is also increasing. The state should strive to establish an egalitarian society. However, most Indian citizens do not have access to credit. At the same time, there is a question that arises about a particular community who are unbanked and unaware of these services due to some religious faith. This paper will talk about the Muslim unbanked community who avoid using banking services due to RIBA (interest), as it is Haram (illegal). The study will inspect the effect of financial inclusion on the unbanked segment of Muslim society. Moreover, fast-rising literature has materialized to inspect its measurement, elements, and effects. The authors used an exploratory research design for the analysis. Hence, a 256 sample size from the Tamil Nadu state of the Muslim unbanked society, who are above 18 in age, has been taken for the study. The cluster sampling technique has been used. T-test, ANOVA, and SEM have been used for finding out the actual result.